A statistical investigation of wind energy potential - Akpinar, E. Kavak (Taylor & Francis Inc, 2006)
In this study, wind speed data from four stations, which are located in Elazig and its close regions, are analyzed. Data are fitted to the Weibull and Rayleigh probability distribution functions. Probability distribution functions are derived from cumulative function and used to calculate the mean wind speed and variance of the actual data. The best way of representing the performance of Weibull and Rayleigh distributions is to use the statistical parameters such as the correlation coefficient (R-2), chi-square (chi(2)) and root mean square error analysis (RMSE). The annual mean wind speed and power are 5.66 m/s and 246.27 W/m(2) for Maden, 3.86 m/s and 98.90 W/m(2) for Agin, 3.14 m/s and 41.37 W/m(2) for Elazig, 2.27 m/s and 15.83 W/m(2) for Keban. Maden has good wind energy potential when it is compared with the other three regions. In general, wind speed is higher during the summer months, notably June and July, and is lower during some winter and spring months. However, for the whole stations, Weibull distribution function was found to be better than Rayleigh distribution function.
Keywords: Weibull and Rayleigh distributions; wind energy; wind speed data